Characteristics of fatal road crashes involving unlicensed drivers or riders: Implications for countermeasures. (August 2018) - Sagberg, Fridulv
Highlights: One out of ten drivers or riders involved in a fatal crash does not hold a valid license. Seventy percent of unlicensed drivers in fatal crashes are influenced by alcohol. Unlicensed drivers are over-represented in speed-related fatal crashes. Electronic driver authentication can prevent unlicensed persons from driving.fective Strategies for a Safer Road Tr. Driver authentication, alcolock and ISA can prevent up to 28% of fatal crashes. Abstract: Drivers or riders without a valid license are involved in 10% of fatal road crashes in Norway. This was shown by an analysis of data from all fatal crashes in the period 2005–2014. A literature review shows that unlicensed drivers have a considerably increased crash risk. Such crashes could be prevented by electronic driver authentication, i.e., a technical system for checking that a driver or rider has legal access to a vehicle before driving is permitted. This can be done by requiring the driver/rider to identify themselves with a national identity number and a unique code or biometric information before driving may commence. The vehicle thereafter verifies license availability and vehicle access by communication with a central register. In more than 80% of fatal crashes with unlicensed drivers/riders, speeding and/or drug influence contributed to the crash. This means that a majority of crashes with unlicensed drivers alternatively could be prevented by already available systems, such as alcolock and speed limit dependent speed adapters. These systems will have a wider influence, by preventing crashes also among licensed drivers. Mandatory implementation of alcolock, speed limiter, and electronic driver authentication in all motorized vehicles is estimated to prevent up to 28% of fatal road crashes, depending on effectiveness of the systems.